The application of solar energy to the design of school buildings, and the development of a model of solar irradiance - Grindley, Peter Columbia (Cranfield University, 1994)
ABSTRACT : THESIS PART ONE. The thermal performances of two schools with central atria, and a typical primary school class- base, were assessed using the SERI-RES computer model. ABSTRACT : THESIS PART TWO. To improve the modelling of sunlight and daylight, measured values of solar radiation, recorded at one minute intervals, were used to examine the relationship attributed to Lui A Jordan(1960), between the fraction of the solar radiation which is received on a horizontal surface, and the equivalent diffuse fraction,